Bacillus cereus in Meat Products: 16S rRNA Phylogenetic Tree analysis and Antimicrobial Investigation of Nisin A, Rosemary Essential Oil and Tetracycline - Sana MH AL-Shimmary 1, Ghusoon A. Abdulhasan2 , Mais E. Ahmed3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In view of the importance of human food poisoning, this study was aimed to isolate B. cereus from meatsources that is economically problem affects both manufacturers and consumers. 16S rRNA was usedto identify bacteria as well as for constructing phylogenetic tree. The activity of different antimicrobialagents (nicin A, Rosemary essential oil and tetracycline) were determined using well diffusion method.16S rRNA analysis was successfully identified the three studied isolates from meat as B. cereus as well asthe phylogenetic tree results observed that bacteria source in meat might be the soil. Rosemary essentialoil at concentration 2000 µg/ml was more effectively then nisin A at 32 mg/ml. In conclusions, the 16SrRNA sequences analysis was efficient for identification of B. cereus. Also, the higher antibacterial effectof Rosemary essential oil against B. cereus need further studies to be used as preservative agent for meatproducts.